Upaya Peningkatan Pemahaman Masyarakat melalui Penyuluhan Pentingnya Imunisasi pada Anak Usia Sekolah - Faiz Nur Hanum; Fathia Maulida; Lilis Suryani (Labor Jurusan Sosiologi, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2022)
One of the Goals of the Sustainable Development Goals is to ensure a healthy life and support well-being for all at all ages, and one of the ways is through immunization. Immunization is an effort to actively generate or increase a person's immunity to a disease, so that when exposed to the disease, he or she will not become sick or only experience mild illness. The purpose of this study was to increase public understanding of the importance of immunization, especially measles and rubella immunization in elementary school age children, by educating parents or guardians of children about the importance of immunization for elementary school age children. The method used is the lecture method (counseling) by following the prescribed health protocol rules. The number of participants in the counseling was 25 people. Counseling activities are carried out first and then followed by immunization activities for children. From all community service activities through counseling carried out, it can be seen that they are obtained in accordance with the objectives, namely the community understands the concept of immunization and is not afraid of the effects caused by immunization.